ESG Ratings and IPO Underpricing: Analyzing the Impact of ESG Metrics on IPO Performance Across Hot and Cold Markets - Häikiö, Juuso (My University, 2025)
In recent years, environmental, social, and governance (ESG) factors have gained increasing attention in both corporate strategy and investment decision-making. While the long-term impact of ESG on firm performance has been widely studied, its short-term effects remain less explored. In particular, limited research has focused on the role of ESG in one of the most critical stages of a company’s lifecycle: the initial public offering (IPO). This thesis examines how ESG ratings influence IPO underpricing and whether this relationship is affected by prevailing market conditions. The theoretical part of the thesis is based on the idea that investors often lack complete information about a company at the time of its IPO. This is called asymmetric information between issuing parties. Because of this, IPO pricing can be uncertain and thus prone to mispricing. To reduce this uncertainty, companies may try to send signals to the market by sharing visible indicators such as ESG scores. This study explores whether ESG information influences how investors price IPOs. The empirical analysis is based on a dataset of U.S. IPOs issued between 2010 and 2023. The data sample consists of 711 companies, of which 301 have an ESG rating from the year of issuing. The data are sourced from the London Stock Exchange Group (LSEG), with IPO information collected from the SDC Platinum database and ESG ratings obtained from Datastream. This thesis employs Ordinary Least Squares (OLS) regression model to investigate the relationship between ESG ratings and IPO underpricing, and to assess whether this relationship is influenced by market conditions. IPO underpricing is measured by comparing the offer price to the closing stock price across several time periods, including the first day, one week, one month, three months, six months, and one year after the IPO. Three regression models are applied: the first examines whether the presence of an ESG rating affects underpricing, the second analyzes the impact of ESG score magnitude and its individual components, and the third includes interaction terms to test whether the effect of ESG varies across hot and cold IPO market periods. The results show that ESG scores are associated with higher underpricing in the short-term, suggesting that investors may react positively to companies that disclose ESG information. However, the actual level of ESG performance does not appear to reduce underpricing in a consistent or meaningful way. Furthermore, there is no evidence that the market environment significantly moderates the impact of ESG on underpricing. These results suggest that ESG acts as a broad signal of firm quality, rather than just impact changes based on market conditions. Thus, while ESG may attract investor interest, its role in IPO pricing is limited and largely depends on presence rather than performance.

Ympäristöön, yhteiskuntaan ja hallintotapaan liittyvät ESG-tekijät ovat saaneet viime aikoina yhä enemmän huomiota yritysten strategisessa päätöksenteossa. ESG:n pitkän aikavälin vaikutuksia yrityksen suorituskykyyn on tutkittu laajasti, kun sen vaikutukset lyhyen aikavälin suorituskykyyn tunnetaan heikommin. Erityisesto ESG:n rooli yrityksen elinkaaren yhdessä kriittisimmässä vaiheessa, listautumisannissa, on tutkittu rajallisesti. Tässä tutkielmassa tarkastellaan, miten ESG luokitukset vaikuttavat listautumisantien alihinnoitteluun sekä vaikuttavatko vallitsevat markkinaolosuhteet tähän yhteyteen. Tutkielman teoreettinen osa pohjautuu ajatukseen, jonka mukaan sijoittajilla ei ole täydellistä tietoa yrityksestä sen listautuessa. Tätä kutsutaan informaation epäsymmetriaksi sidosryhmien välillä. Tästä syystä listautumisten hinnoittelu voi olla epävarmaa, mikä altistaa hinnoitteluvirheille. Vähentääkseen tätä epävarmuutta yritykset voivat pyrkiä signaloimaan omaa laatuaan käyttämällä ESG-luokittelua. Tässä tutkimuksessa selvitetään, vaikuttaako ESG-tieto siihen, miten sijoittajat hinnoittelevat listautumisanteja. Empiirinen analyysi perustuu aineistoon Yhdysvaltojen markkinoilta vuosina 2010–2023 toteutetuista listautumisista. Aineisto sisältää 711 yritystä, joista 301:llä on ESG-luokitus listautumisvuodelta. Aineisto on peräisin London Stock Exchange Groupilta (LSEG), ja tiedot listautumisista on kerätty SDC Platinum -tietokannasta sekä ESG-luokitukset Datastream-palvelusta. Tutkielmassa hyödynnetään OLS-regressiomallia, jolla tutkitaan ESG-luokitusten ja alihinnoittelun välistä yhteyttä sekä arvioidaan, vaikuttavatko markkinaolosuhteet tähän yhteyteen. Alihinnoittelu lasketaan vertaamalla osakkeen listautumishintaa useisiin eri ajanjaksoihin: ensimmäiseen päivään, viikkoon, kuukauteen, kolmeen kuukauteen, kuuteen kuukauteen sekä vuoteen. Käytössä on kolme regressiomallia, joista ensimmäinen tutkii, vaikuttaako ESG-luokituksen olemassaolo alihinnoitteluun. Toinen analysoi ESG-pistemäärän ja sen yksittäisten komponenttien vaikutusta, ja kolmas tuo mukaan interaktiotermit, joilla testataan, vaihteleeko ESG:n vaikutus kuumien ja kylmien IPO-markkinajaksojen välillä. Tulosten mukaan ESG-luokitukset ovat yhteydessä korkeampaan alihinnoitteluun lyhyellä aikavälillä, mikä viittaa siihen, että sijoittajat reagoivat positiivisesti yrityksiin, jotka raportoivat ESG tietoja. Kuitenkaan varsinaisella ESG-suorituskyvyn tasolla ei näytä olevan johdonmukaista tai merkittävää vaikutusta alihinnoittelun vähentämiseen. Lisäksi tulokset eivät anna näyttöä siitä, että markkinaympäristö merkittävästi muuttaisi ESG:n vaikutusta alihinnoitteluun. Tulokset viittaavat siihen, että ESG toimii laajana signaalina yrityksen laadusta eikä pelkästään markkinaolosuhteiden mukaan muuttuvana tekijänä. Näin ollen, vaikka ESG saattaa herättää sijoittajien kiinnostusta, sen rooli IPO-hinnoittelussa on rajallinen ja riippuu pitkälti ESG:n olemassaolosta ennemmin kuin sen suorituskyvystä.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance